The effect of different timing of blood transfusion on oncological outcomes of patients undergoing radical cystectomy for bladder cancer: a systematic review and meta-analysis - Ma, Si-Yang; An, Ye; Sun, Jian-Xuan; Xu, Meng-Yao; Liu, Chen-Qian; Xu, Jin-Zhou; Zhong, Xing-Yu; Zeng, Na; He, Hao-Dong; Xia, Qi-Dong; Wang, Shao-Gang (Frontiers in Oncology, 2023)
Highlights This meta-analysis and systematic review aim to analyze the association between BT and oncological outcomes of patients undergoing RC for bladder cancer, and tries to find out whether the timing of blood transfusion could also have an effect on this relationship. A total of 20 retrospective studies from online databases and other sources are identified and enrolled in this study. The results show that BT administration during RC operation or perioperative period is significantly associated with worse oncological outcomes including ACM, CSM and DR. Background Bladder cancer is one of the most common urological malignancies. Radical cystectomy (RC) remains the main treatment for localized muscle-invasive bladder cancer (MIBC) or high-grade non-muscle-invasive bladder cancer (NMIBC). In the process of RC, the administration of blood transfusion (BT) is sometimes needed, however, it may cause transfusion-related complications or lead to worse oncological outcomes. This meta-analysis and systematic review aims to give a comprehensive insight into the association between BT and oncological outcomes of patients undergoing RC, and tries to find out whether the timing of blood transfusion could also have an impact on this association. Methods This systematic review and meta-analysis were carried out according to the PRISMA 2020 reporting guideline. We have searched four bibliographic databases including PubMed (Medline), EMBASE, Cochrane Library, and Web of Science with no language limitation. Studies investigating the association between BT and oncological outcomes of patients undergoing RC are identified and included in this research from inception through March 20, 2023. This research calculates the pooled hazard ratios (pHR) and 95% confidence intervals (95% CI) of all-cause mortality (ACM), cancer-specific mortality (CSM) and disease recurrence (DR) using Random Effects models or Fixed Effects models. Subgroup analyses stratified by parameters such as timing of transfusion are also conducted. This meta-analysis was registered with PROSPERO, CRD42022381656. Results A total of 20 retrospective studies from online databases and other sources are identified and enrolled in this study. Results show that blood transfusion significantly increased the risks for ACM (HR = 1.33, 95% CI: 1.23-1.44), CSM (HR = 1.25, 95% CI: 1.15 – 1.35) and DR (HR = 1.26, 95% CI: 1.15 – 1.38). However, when stratified by the timing of BT, we find that only intraoperative and perioperative transfusion significantly increased in risks for worse prognosis, while postoperative transfusion raised none of the risks of ACM (HR = 1.26, 95% CI: 0.92-1.73), CSM (HR = 1.08, 95% CI: 0.93-1.26) nor DR (HR = 1.08, 95% CI: 0.90-1.29) significantly. Conclusion BT administration during RC operation or perioperative period is significantly associated with worse oncological outcomes including ACM, CSM and DR. Clinicians should consider carefully when deciding to administrate BT to patients undergoing RC and carry out according to current guidelines.